Finite element to predict damage of a polycarbonate armor plate subjected to impact - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Numerical studies on the response of annor systems made up of PC and PMMA were reported [1] where smooth particle hydrodynamics (SPH) was used to simulate the response of PC and PMMA layers and it has been found that many existing material models can reproduce a close range results at the initial stage of simulations. Further numerical results based upon the experiments [2] have been reported by [3] where the effects of varying support configurations have been investigated on the plastic failure of the circular steel plates. Circular plates subjected to dense fragment cluster impact [4, 5] investigates the failure process of almor plates subjected to a fragment cluster consisting of many projectiles impacting the plate simultaneously. Test results indicate that the impulse and the rate of energy deposition on the target and the impacting duration ofthe ti-agment cluster are the most important factors